Monetary Policy Committee and Monetary Policy Conduct in Nigeria: A Preliminary Investigation (2014)
The study provides an incisive but preliminary investigation into the activities of the monetary policy committee of the central bank of Nigeria and the implications for monetary policy, using the standard deviation measure of volatility and the ordinary least square method. The findings show that the ‘internal’ members and majority of the ‘external’ members have different preferences as shown in the voting patterns. Also, there has been reduction in inflation, money and stock markets volatilities since the operations of the committee became more visible. Furthermore, there is no structural break in both the money and stock markets in the period when the central bank started releasing the personal statements and voting pattern of the committee members. The policy implication of these results is that the transparency with which the monetary policy committee has operated since 2011 has boosted policy credibility due to the reduction in markets volatility. Nevertheless, there is need for the individual committee members to be more visible to the public through different platforms as this will further improve the central bank’s communications strategy.